Caracterização da cinza de bagaço de cana-de-açúcar e aplicação no solo - Oliveira, Darlene Lopes do Amaral [UNESP] (2014)
The increased use of sugarcane bagasse for electric energy production in the State of São Paulo has resulted in large amounts of ashes that requires its proper handling and disposal. The current target of this large-scale residue has been its use in sugarcane soil areas, though this method is not authorized by the country's environmental agencies or by the Ministry of Agriculture and the assessments about advantages or disadvantages of its application are scarce. This research was proposed to evaluate the effects of sugar bagasse ashes (SBA) application in different doses on chemical soil attributes. Three studies were proposed for this: a)The incubation test to evaluate the biodegradation of the organic fraction of the SBA; b)Tests in soil columns with preserved structure using completely randomized design with 3 replications in order to detect possible changes in water percolated, and its possible implication in vegetation ecological conditions on soils, representing the region of Jaboticabal-SP (Oxisol); and c)Field trial in two areas under Ultisol with citrus cultivation with different SBA managements (incorporated and surface application) through the randomized block designs with 5 repetitions. The SBA was characterized through different physical chemical methods, to identify their organic and inorganic fraction. Were evaluated in the studies the effect of different doses of SBA (0, 5, 10, 20, 40 and 80 Mg ha-1) as regards the behavior of metals: toxic (Cr) and phytotoxic (Zn, Cu, Mn and Ni); the semimetal (Si) and anions (SO42- and PO42-). The results showed that the SBA is rich in SiO2 (82.2%) with predominance of crystalline quartz and potassium silicate in lower concentration. The mineralization fraction of C in C-CO2 was less than 1.6% in 182 days of incubation and this indicated that the SBA contributes to increase the stocks of soil organic matter. The carbon mineralization rate added by sugarcane bagasse ashes has ...